Photocatalytic disinfection treatments: viability, cultivability and metabolic changes of e. coli using diferent mesurements methods (2011)
In this work, the oxidative stress was produced by the illumination of either fixed TiO₂ or suspended TiO₂, and the relation between cultivability and viability under oxidative conditions was studied using a Direct Viable Count (DVC) and Fluorescence In Situ Hybridisation (FISH) methods. Under certain oxidative conditions simulating incomplete treatments, viable cells that had lost their cultivability were observed to recover all of their physiological functions when transferred to fresh nutrient media. Moreover, alterations in the nutrient assimilation processes were studied by 1H-NMR during and after the photocatalytic treatment. This allowed us to shed some light on how the damage chain propagates during the treatment. This work demonstrate that the Standard Plate Count (SPC) method commonly used to estimate the c ell populations during disinfection processes is ill adapted, whereas the FISH-DVC pair offers a reliable alternative.